Discrete optimization problem - Kotina, E.D. (Вопросы атомной науки и техники, 2004)
In the paper a mathematical model is considered that allows simultaneous optimization of a program motion and
an ensemble of perturbed motions. Analytical expressions for functional variations are suggested that help constructing various directed methods of optimization. Given mathematical apparatus can be effectively used in the optimization of the dynamics of charged particles in linear accelerators. Запропонована математична модель оптимізації програмного руху (руху синхронної частки) і ансамблю обурених
рухів. Розглядаються мінімаксні функціонали, що дозволяють оцінювати динаміку часток по “найгіршим” частках. Предлагается математическая модель оптимизации программного движения (движения синхронной частицы) и ансамбля возмущенных движений. Рассматриваются минимаксные функционалы, позволяющие оценивать динамику частиц по “наихудшим” частицам.